2012
DOI: 10.1097/aln.0b013e3182605afe
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vasoconstriction Affects Near-infrared Spectroscopy Determined Cerebral Oxygen Saturation during Administration of Norepinephrine

Abstract: The results confirm that spatially resolved near-infrared spectroscopy detects cerebral deoxygenation with systemic hypoxic exposure and hyperventilation. However, a commonly used vasopressor norepinephrine disturbs skin oxygen saturation to an extent that influences scO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 39 publications
(54 reference statements)
2
91
3
Order By: Relevance
“…The authors suggested that both norepinephrine and hyperthermia affected skin oxygenation and subsequently influenced SctO 2 readings by reducing the values. 17 There are no regulatory standards thus far with respect to error in the precision of cerebral oximetry readings. Nevertheless, when examining the pulse oximeter, a monitor similar in design to a cerebral oximeter, the regulatory standards permit SpO 2 values to vary from baseline up to 3.5% according to the U.S. Food and Drug Administration and up to 4% according to the International Organization for Standardization.…”
Section: Extracranial Contamination Of Nirs 27mentioning
confidence: 99%
“…The authors suggested that both norepinephrine and hyperthermia affected skin oxygenation and subsequently influenced SctO 2 readings by reducing the values. 17 There are no regulatory standards thus far with respect to error in the precision of cerebral oximetry readings. Nevertheless, when examining the pulse oximeter, a monitor similar in design to a cerebral oximeter, the regulatory standards permit SpO 2 values to vary from baseline up to 3.5% according to the U.S. Food and Drug Administration and up to 4% according to the International Organization for Standardization.…”
Section: Extracranial Contamination Of Nirs 27mentioning
confidence: 99%
“…In this study, blood pressure was unaffected during phenyleprine infusion. Similarly, intracarotid injection of sodium nitroprusside in humans does not increase cerebral blood flow [7].…”
Section: H P Grocottmentioning
confidence: 99%
“…Moreover, an epior a subdural haematoma can have adverse effects; in such cases, the cerebral cortex is likely to be beyond the range of radiation emitted by the sensor. The other factors limiting the value of brain saturation measurements involve brain oedema and local disorders of perfusion resulting from the presence of atherosclerotic lesions or arterial embolism [9].…”
Section: Limitations Of Nirs For Assessment Of Brain Saturationmentioning
confidence: 99%
“…In cases of cerebral cortex atrophy, often observed in elderly patients, the range of proton beam can be insufficient to assess cortex oxygenation ( Fig.2) [9]. It has been found that NIRS monitor readings in the elderly can paradoxically decrease during cooling and increase during re-warming (brain cooling reactivity), which indicates the presence of significant cortical atrophies and limits the possibility of brain oximetry interpretation [5].…”
Section: Limitations Of Nirs For Assessment Of Brain Saturationmentioning
confidence: 99%